(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2011)
Capital is a property bank is very important, because it is part of the liquidity in the bank, which is a line of defense in the bank and secured against any losses that may be exposed to the banks, and in the case of low value of any item of the assets and the lack of a dedicated absorb the decline, while play a key role to some extent in the financing of fixed assets and in particular the relative importance of fixed assets is relatively small compared to the size of bank assets. This study sought to measure the adequacy of the capital property is banking on the profitability of commercial banks through the selection of Bank of the Middle East Iraqi investment model for the research sample. Has been used five quantitative measures to determine the durability of capital property in the Commercial Bank, a percentage of capital property to total assets, the ratio of capital property to the assets of the risk, the ratio of capital property to the deposits, the ratio of capital property to the loans, the ratio of capital property to the total investment. Was measured effect of the change in the capital on the profitability of the bank property by dividing the rate of return on capital property on the rate of return on investment. The results of analysis of these indicators reflect most of the results of analysis of indicators of the bank.